2014
DOI: 10.1177/1524839913518559
|View full text |Cite
|
Sign up to set email alerts
|

Can the Inpatient Hospital Setting Be a Golden Opportunity to Improve Colon Cancer Screening Rates in the United States?

Abstract: The time of hospitalization is a potential "golden opportunity" to counsel patients and promote colon cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
3
3
0
Order By: Relevance
“…This finding is in contrast with a previous study where only one-fifth of the non-adherent hospitalized patients reported a willingness to undergo inpatient colonoscopy. 15 However, overall findings from our study are consistent with a previous study evaluating preferences of hospitalized women toward other cancer screening as noted for breast cancer. 26 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in contrast with a previous study where only one-fifth of the non-adherent hospitalized patients reported a willingness to undergo inpatient colonoscopy. 15 However, overall findings from our study are consistent with a previous study evaluating preferences of hospitalized women toward other cancer screening as noted for breast cancer. 26 …”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies have evaluated the prevalence of non-adherence to CRC screening among the hospitalized population. 15 , 16 Results from our study were consistent with prior study, reiterating the fact that a pattern of adherence to CRC screening among hospitalized populations does not change over time. 15 Perceived risk and knowledge about CRC are thought to influence the perceptions of screening necessity and are crucial to adopting preventive behavior.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hospitalization is a unique situation that creates an environment in which patients not only have access to healthcare resources but they also are extremely receptive to recommendations by their hospital providers. Prior studies evaluating the preferences of hospitalized women regarding cancer screening have reported that hospitalized women are enthusiastically receptive to screening recommendations during a hospital stay and amenable to having screening tests done during their hospital visit or after hospital discharge if due and offered 27–29 . As such, all efforts should be made to capitalize on hospitalization as an opportunity to improve cancer screening in general because some of the barriers such as transportation, scheduling, and counseling about screening tests can be overcome during a hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Multilevel screening strategies are warranted to address the barriers affecting CRC screening adherence and exploring this missed opportunity to counsel patients and engage in discussion about CRC screening could help improve CRC screening especially in hospitalized women. 17 , 18 Similar studies evaluating breast cancer screening have demonstrated that majority of hospitalized women were willing to have inpatient screening mammogram if offered during hospital stay. 16 , 19 As screening colonoscopy procedure is usually performed in the outpatient setting, anticipated additional cost associated with inpatient screening colonoscopy would be likely from facility charge, type of sedation required during the procedure, polyp removal, and possible increase in the length of stay in the hospital.…”
Section: Discussionmentioning
confidence: 94%